Vinblastine monotherapy induction prior to radiotherapy for patients with intracranial germinoma during the COVID‐19 pandemic. Issue 1 (14th September 2021) - Murray, Matthew J.; Moleron, Rafael; Adamski, Jennifer; English, Martin; Burke, G. A. Amos; Cross, Justin; Ajithkumar, Thankamma; Stoneham, Sara; Nicholson, James C.
Abstract: Background: Patients with localized intracranial germinoma have excellent survival. Reducing treatment burden and long‐term sequelae is a priority. Intensive inpatient chemotherapy (e.g., carboPEI = carboplatin/etoposide/ifosfamide) has been effectively employed to reduce radiotherapy treatment volume/dose. Outpatient‐based carboplatin monotherapy is associated with excellent outcomes in metastatic testicular seminoma (an identical pathology), and successful vinblastine monotherapy induction (with 77% tumor volume reduction after just two weekly vinblastine doses) has recently been reported in an intracranial germinoma patient. Methods: Adapted UK guidelines for germ cell tumor management were distributed during the COVID‐19 pandemic, including nonstandard treatment options to reduce hospital visits and/or admissions. This included vinblastine monotherapy for intracranial germinoma (6 mg/m 2 intravenously, or 4 mg/m 2 for moderate count suppression, delivered weekly). We describe two such patients treated using this approach. Results: A 30‐year‐old male with a localized pineal tumor received 12‐week vinblastine induction, with >60% volume reduction, prior to definitive radiotherapy. A 12‐year‐old female with a metastatic suprasellar tumor and progression at all sites of disease whilst awaiting proton radiotherapy received two vinblastine doses with good early response, including 36% primary tumor volume reduction. The patients tolerated vinblastine well. Conclusion: Patients with intracranial germinoma have excellent outcomes, and reduction of late effects remains a priority. The description of vinblastine monotherapy in these intracranial germinoma patients warrants further exploration.